Theatre of War: High Culture and Popular Entertainment in the Spectacle of Kosovo - Barton Catmur, Will (Javnost-The Public, 2000)
It is no accident that we speak of "Theatres of War," for war is surely the ultimate fiction. I have been hideously fascinated by the way in which, in the absence of any significant external threat to justify state violence, aggressive war has become a form of spin doctoring by other means. Postmodern war, like all other parts of the Spectacle, can no longer be understood as "politics by other means." Such conflicts do make sense, but only at another level of explanation -- that of their consumption. They stand in a line of development that goes back to the earliest dramatic rituals and comes to us through tragedy, opera, film and TV drama. Like soap opera, they need no end, for their characters are equally plastic and universal. Only for the people whose homes, lives and deaths serve as the raw material for this production, have the actions any meaning beyond the Spectacle.